Assessment And Differentiated Learning For Teachers In Vocational Secondary Schools - Reni Dwi Susanti; Marhan Taufik; Akhsanul In'am (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
This research aims to explore the application of differentiated instruction and its assessment in Vocational High Schools, focusing on teachers' understanding, challenges in implementation, the use of differentiated assessment, and its impact on student engagement and learning outcomes. The study employs a qualitative descriptive method, with data collected through observations, interviews, and document analysis. Findings indicate that teachers understand the fundamental principles of differentiated instruction and have attempted to apply them through various approaches, such as grouping students based on ability levels and adjusting materials. However, the main challenges faced include time constraints, limited resources, and a lack of training to effectively implement differentiation. Differentiated assessment has also been applied in the form of formative and project-based assessments, though teachers report difficulties in providing in-depth feedback within limited timeframes. Positive impacts from the application of differentiated instruction are seen in increased student interest and motivation, as well as improved learning outcomes. This study provides theoretical contributions by supporting the application of differentiated instruction principles within the vocational education context and offers suggestions to enhance teacher training and resource development for more effective differentiation. The results of this study are expected to serve as a reference for developing more inclusive and adaptive learning approaches in vocational school and other educational institutions.